Can galectin‐3 be a useful marker for conventional papillary thyroid microcarcinoma?. Issue 2 (17th December 2015) - Gweon, Hye Mi; Kim, Jeong‐Ah; Youk, Ji Hyun; Hong, Soon Won; Lim, Beom Jin; Yoon, Sun Och; Park, Young Mi; Son, Eun Ju
Abstract : Background: Galectin‐3 staining of fine‐needle aspiration (FNA) samples is very useful for diagnosis of thyroid malignancy. As reported in several studies, galectin‐3 is associated with prognostic factor in papillary thyroid carcinoma, but its expression and prognostic role has not been evaluated in papillary microcarcinoma (PTMC). This study was performed to investigate the prevalence of galectin‐3 in preoperative ultrasonography (US)‐guided FNA cytology and to evaluate the association between galectin‐3 expression and prognostic factors of PTMC. Methods: Between January 2011 and December 2012, 440 conventional PTMCs which had undergone US‐guided FNA with galectin‐3 analysis and underwent subsequent surgery were enrolled. Preoperative US features and clinicopathologic results including extrathyroidal extension and lymph node metastasis were compared between galectin‐3 positive and galectin‐3 negative PTMC. Results: Of the 440 PTMCs, 201 (45.7%) PTMCs had galectin‐3 positivity in preoperative FNA samples. There was no significant difference in US features between galectin‐3 positive and negative PTMC. Galectin‐3 expression had no significant association with prognostic factors such as extrathyroidal extension (44.8% vs. 44.8%, P = 0.999) and lymph node metastasis (25.9% vs. 26.8%, P = 0.914) in conventional PTMC. Conclusion: Preoperative galectin‐3 analysis using FNA cytology may be not advisable in patients with conventional PTMC. Diagn. Cytopathol. 2016;44:103–107. © 2015 Wiley Periodicals, Inc.